Neural Processing of Congruent and Incongruent Audiovisual Speech in School‐Age Children and Adults. (27th September 2017) - Heikkilä, Jenni; Tiippana, Kaisa; Loberg, Otto; Leppänen, Paavo H. T.
Abstract: Seeing articulatory gestures enhances speech perception. Perception of auditory speech can even be changed by incongruent visual gestures, which is known as the McGurk effect (e.g., dubbing a voice saying /mi/ onto a face articulating /ni/, observers often hear /ni/). In children, the McGurk effect is weaker than in adults, but no previous knowledge exists about the neural‐level correlates of the McGurk effect in school‐age children. Using brain event‐related potentials, we investigated change detection responses to congruent and incongruent audiovisual speech in school‐age children and adults. We used an oddball paradigm with a congruent audiovisual /mi/ as the standard stimulus and a congruent audiovisual /ni/ or McGurk A/mi/V/ni/ as the deviant stimulus. In adults, a similar change detection response was elicited by both deviant stimuli. In children, change detection responses differed between the congruent and the McGurk stimulus. This reflects a maturational difference in the influence of visual stimuli on auditory processing.